Effect of Puddling and Direct Sowing of Rice on Soil Physical Health and Water Productivity of Rice-Wheat Cropping System under Different Irrigation Regimes - and D.K. Singh, K.K. Bandyopadhyay*, A. Sarangi, Dinesh (Journal of the Indian Society of Soil Science, 2019)
A field experiment was conducted during 2012-13 to 2013-14 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of three rice cultivation methods, viz., direct seeded rice (DSR), system of rice intensification (SRI) and conventional puddled transplanted rice (PTR) under adequate and deficit irrigation on soil structure and the water productivity of rice-wheat cropping system (RWCS). Results showed that mean weight diameter and percentage of macro-aggregate stability decreased under PTR (0.86 mm and 71.8%) and SRI (0.85 mm and 74.2%) compared with DSR (1.00 mm and 79.5%) method. The SRI method resulted in significantly higher yield of rice than PTR and DSR by 15.9 and 42.6 per cent, respectively. Water productivity of rice under SRI and DSR was significantly higher than PTR by 41.1 and 34.1 per cent, respectively. The grain yield and water productivity of wheat following DSR were significantly higher than those following PTR by 23.7 and 11.8 per cent, respectively. Moreover, considering RWCS as a whole, DSR resulted in significantly higher system water productivity (7.01 kg ha-mm-1) and significantly lower water use (1390 mm) compared with PTR and SRI methods.